Molecular characterization of peroxisome proliferator activated receptor gamma2 (PPARγ2) promoter from bovine - Ismail, Ida Shazrina; Arip, Yahya Mat; Muhammad, Tengku Sifzizul Tengku (Penerbit Universiti Sains Malaysia, 2004)
Peroxisome proliferator activated receptor gamma (PPARγ) is a member of the PPAR subfamily of nuclear hormone receptors (Schoonjans et al., 1996a). So far, two PPARγ isoforms; γ1 and γ2, have been cloned in bovine and produced by alternative promoter usage and differential splicing of a single gene (Sundvold et al., 1997). PPARγ functions by forming heterodimeric complexes with 9-cis-retinoic acid X receptors (RXRs).